Gender Differences in the Risk of Coronary Artery Disease in Iran - J Soares; Ö Sundin; AA Karimi; SE Kassaian; A Ponce De Leon; SH Abbasi; G Macassa (Tehran University of Medical Sciences, 2012)
Background: Given gender differences in the risk of coronary artery disease (CAD), the present study sought to investigate these dissimilarities amongst patients who underwent angiography at a major, tertiary heart hospital in Iran.Methods: Between 2005 and 2010, 44,820 patients who underwent coronary angiography were enrolled in a registry. Pre-procedural data such as demographics, CAD risk factors, presenting symptoms, and laboratory tests, as well as post-procedural data were collected. The data were, subsequently, compared between the men and women.Results: Out of the 44,820 patients (16,378 women), who underwent coronary angiography, 37,358 patients (11,995 women) had CAD. Amongst the CAD patients, the females were not only significantly older, less educated, and more overweight than were the males but also had higher levels of triglyceride, cholesterol, low-density lipoprotein, high-density lipoprotein, and fasting blood sugar (P< 0.001). Of all the risk factors, hypertension and diabetes mellitus showed the strongest association in our female CAD patients (OR=3.45, 95%CI: 3.28-3.61 and OR=2.37, 95%CI: 2.26-2.48, respectively). Acute coronary syndrome was more prevalent in the men (76.1% vs. 68.6%, P< 0.001), and chronic stable angina was more frequent in the females (31.4% vs. 23.9%, P< 0.001). With respect to post-procedural recommendations, the frequency of recommendations for non-invasive modalities was higher in the females (20.1% vs. 18.6%, P< 0.001).Conclusion: Hypertension and diabetes mellitus had the strongest association with CAD in our female patients. In the extensive CAD patients, medical treatment was recommended to the women more often.